Case Report: Inhaled salbutamol in the successful treatment of life-threatening acute hyperkalaemia in an anaesthetised horse - Rollet, Madelyn; Flyps, Jana; Vernemmen, Ingrid; van Loon, Gunther; Schauvliege, Stijn (Frontiers in Veterinary Science, 2026)
Hyperkalaemia is an uncommon complication of general anaesthesia in healthy horses. This case report describes the occurrence of life-threatening acute hyperkalaemia in a 13-year-old, female French Trotter anaesthetised for experimental right and left atrial 3D electro-anatomical mapping. Intra-operative development of hyperkalaemia (7.55 mmol/L) (Ref. 3.00–4.00 mmol/L) with atrial standstill on ECG necessitated transvenous ventricular pacing while initial treatment with insulin and glucose was initiated. Plasma potassium levels continued to increase (8.00 mmol/L) prompting adjunctive treatment with 5 μg/kg of inhaled salbutamol and intravenous furosemide 0.93 mg/kg. Eight minutes after salbutamol administration, return of spontaneous atrial contraction was observed on echocardiography and plasma potassium concentration rapidly decreased on serial blood samples. To the authors’ knowledge, this is the first case report documenting the use of inhaled salbutamol in the treatment of life-threatening acute hyperkalaemia in an anaesthetised horse.